Interspecies In Vitro Evaluation of Stereoselective Protein Binding for 3,4-Methylenedioxymethamphetamine - Wan Raihana Wan Aasim; Soo Choon Tan; Siew Hua Gan (Journal of Chemistry)
Abuse of 3,4-methylenedioxymethamphetamine (MDMA) is becoming more common worldwide. To date, there is no information available on stereoselectivity of MDMA protein binding in humans, rats, and mice. Since stereoselectivity plays an important role in MDMA’s pharmacokinetics and pharmacodynamics, in this study we investigated its stereoselectivity in protein binding. The stereoselective protein binding of rac-MDMA was investigated using two different concentrations (20 and 200 ng/mL) in human plasma and mouse and rat sera using an ultrafiltration technique. No significant stereoselectivity in protein binding was observed in both human plasma and rat serum; however, a significant stereoselective binding (p<0.05) was observed in mouse serum. Since the protein binding of MDMA in mouse serum is considerably lower than in humans and rats, caution should be exercised when using mice for in vitro studies involving MDMA.